WDW XXV - In light of 25 years - Ayas, Defne 1976-; Saelemakers, Samuel (Witte de With Center for Contemporary Art, 2016)
During this 25th anniversary year, Witte de With set out to examine its history, dedicating its ground-floor gallery to a series of commissioned presentations by a select group of international contemporary artists, including Özlem Altin, Wineke Gartz, Camille Henrot, Germaine Kruip, Mahony, Raimundas Malašauskas, Zin Taylor, Freek Wambacq, and Xu Zhen. Each participant created a new work that analysed certain sediments of contemporary art history. Presented on a large-scale double-sided light box these anniversary commissions were visible to the city day and night. The publication WDWXXV: In Light Of 25 Years documents these newly commissioned works which respond in varied ways to developments in contemporary art, its landscape and possibilities today, departing from Witte de With’s quarter century of exhibition history. Alongside the reproduced individual works and introductions by Director Defne Ayas and Curator Samuel Saelemakers, the publication reintroduces the element of space, prominent in the In Light Of 25 Years project.